The Effect of NPK 12-6-27 Fertilization on the Growth of Oil Palm Plants in the Main Nursery on Bogor Acid Dry Land - Joko Purnomo; Nurjaya Nurjaya; Diah Setyorini (Jurnal Penelitian Pendidikan IPA, 2022)
Research on the response to NPK 12-6-27 fertilization on oil palm seedlings was carried out on Oxisols acid dry soil from Bogor. Oil palm seedlings were planted in pots at the age of 3 months after the prenursery phase and maintained for 6 months. The purpose of the study was to determine the response of the NPK 12-6-27 fertilizer formula to the growth of oil palm plants in the main nursery and to obtain information on the optimum dose. The experimental design used was a randomized block with 7 treatments which were repeated 8 times. The treatments consisted of control, standard NPK, and five doses of NPK fertilizer formula 12-6-27. The results showed that the soil has a low level of soil fertility. Soil fertility constraints include acid soil pH (pH-H2O = 4.7), level of C and N, P and K, cation exchange and cation exchange capacity (CEC) were low and high level of Al saturation (54%). At 6 months after application (BSA) fertilizers, application of NPK significantly increased oil palm plant height. The plant height in the Control treatment was about 71.4 cm and increased to 86.0 – 93.4 cm in the standard NPK and NPK 12-6-27 treatments. The standard NPK and NPK 12-6-27 treatments did not produce significantly different plant heights. The Control treatment resulted in stem dry weight of 114.3 g/pot and significantly increased to 158.2 – 207.0 g/pot with standard NPK and NPK 12-6-27. Fertilization of NPK 12-6-27 doses of 1.5 x and 2x resulted in plant dry weight of 206.3 g/pot and 207.0 g/pot higher and significantly different than standard NPK which resulted in plant dry weight of 158.2 g/pot. The RAE value of NPK 12-6-27 fertilizer is 120 – 211 higher than the standard NPK namely 100. The optimum dose of NPK 12-6-27 is 51 g/pot given for 6 months in the main nursery